Small nuclear ribonucleoproteins and heterogeneous nuclear ribonucleoproteins in the amphibian germinal vesicle: loops, spheres, and snurposomes (The Rockefeller University Press, 1991)
We have examined the distribution of snRNPs in the germinal vesicle (GV) of frogs and salamanders by immunofluorescent staining and in situ nucleic acid hybridization. The major snRNAs involved in pre-mRNA splicing (U1, U2, U4, U5, and U6) occur together in nearly all loops of the lampbrush chromosomes, and in hundreds to thousands of small granules (1-4 microns diameter) suspended in the nucleoplasm. The loops and granules also contain several antigens that are regularly associated with snRNAs or spliceosomes (the Sm antigen, U1- and U2- specific antigens, and the splicing factor SC35). A second type of granule, often distinguishable by morphology, contains only U1 snRNA and associated antigens. We propose the term "snurposome" to describe the granules that contain snRNPs ("snurps"). Those that contain only U1 snRNA are A snurposomes, whereas those that contain all the splicing snRNAs are B snurposomes. GVs contain a third type of snRNP granule, which we call the C snurposome. C snurposomes range in size from less than 1 micron to giant structures greater than 20 microns in diameter. Usually, although not invariably, they have B snurposomes on their surface. They may also contain from one to hundreds of inclusions. Because of their remarkably spherical shape, C snurposomes with their associated B snurposomes have long been referred to as spheres or sphere organelles. Most spheres are free in the nucleoplasm, but a few are attached to chromosomes at specific chromosome loci, the sphere organizers (SOs). The relationship of sphere organelles to other snRNP- containing structures in the GV is obscure. We show by immunofluorescent staining that the lampbrush loops and B snurposomes also react with antibodies against heterogeneous nuclear ribonucleoproteins (hnRNPs). Transcription units on the loops are uniformly stained by anti-hnRNP and anti-snRNP antibodies, suggesting that nascent transcripts are associated with hnRNPs and snRNPs along their entire length, perhaps in the form of a unitary hnRNP/snRNP particle. That B snurposomes contain so many components involved in pre- mRNA packaging and processing suggests that they may serve as sites for assembly and storage of hnRNP/snRNP complexes destined for transport to the nascent transcripts on the lampbrush chromosome loops.